2019
DOI: 10.1002/eco.2122
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of rare flood meadow species distribution by a combined habitat surface water–groundwater model

Abstract: Floodplains are highly complex and dynamic systems in terms of their hydrology.Thus, they comprise a wide habitat heterogeneity and therefore harbour highly specialized species. For future projections of habitat and species diversity, processbased models simulating ecohydrological conditions and resulting habitat and species distributions are needed. We present a new modelling framework that includes a physically based, surface water-groundwater model coupled with a habitat model.Using the model framework, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…The daily groundwater level of each of the 254 plots was estimated as the inverse-distance weighted mean of the three nearest groundwater points. For each plot, we calculated three relevant hydrological predictors for species distribution (following Gattringer et al (2019)):…”
Section: Hydrological Variablesmentioning
confidence: 99%
“…The daily groundwater level of each of the 254 plots was estimated as the inverse-distance weighted mean of the three nearest groundwater points. For each plot, we calculated three relevant hydrological predictors for species distribution (following Gattringer et al (2019)):…”
Section: Hydrological Variablesmentioning
confidence: 99%
“…As shown by Gattringer et al. (2019) predictors from an IHM improve habitat modeling in comparison to groundwater, or surface‐water‐only predictors scenarios. Our results indicated that in some scenarios the trends were not present in water levels, or discharges while they were present in the persistence of dominant water sources.…”
Section: Discussionmentioning
confidence: 89%
“…Modeling of vegetation development under climate change may be hampered because studies using the process-based model (Politti et al, 2014), a statistical approach (Mosner et al, 2015) do not include hydrodynamic feedback between water from different sources while focusing only on the river, or groundwater levels. As shown by Gattringer et al (2019) predictors from an IHM improve habitat modeling in comparison to groundwater, or surface-water-only predictors scenarios. Our results indicated that in some scenarios the trends were not present in water levels, or discharges while they were present in the persistence of dominant water sources.…”
Section: Implications For Ecological Processesmentioning
confidence: 96%
“…In addition, the altered dynamics of riparian ecosystems can trigger the establishment and spread of non-native tree species in floodplains [6,[9][10][11][12][13][14]. On top of this, climate change induced impacts on the alluvial plant communities add to the uncertainty about adequate conservation and restoration measures [15,16]. Whilst the recovery of floodplain forests is one of the most important objectives in alluvial restoration and for the conservation of biodiversity [4], the complex interactions between the physical environment and biological processes are not fully understood, which complicates restoration efforts [17].…”
Section: Introductionmentioning
confidence: 99%